Analisis Hasil Belajar Siswa pada Pembelajaran Operasi Aljabar Melalui Penerapan Fase-Fase Belajar Gagne - Hutapea, Nahor Murani (Jurnal Pilar Sains, 2005)
An Analysis Learning Outcomes on Intructional Algebra Operation of Gagne Phases Aplication. Thisresearch was carried out the respond and activity student and learning outcome on instructionalalgebra operation of gagne phases application in September – October 2003 on SMP Kalam KudusPekanbaru. Sample of the research is the third studens (IIIB experiment class, IIIC control class). Thedata was conducted with test (pre test, post test). Observation and questioner methods. The dataanalyzed by descriptive statistic and inferensial. Result showed the students actrivity is effective andthe positively students responses. Gagne phases application is significant to increase learning outcomestudents (18.101 > 4.110, α = 0.05) of algebra operation.